Phase Transformation and the Heat and Mass Transfer in the Ice, Water and Brine System. Issue 19 (12th November 2020) - Yun, Xiao; Brooks, Sam; Quarini, Giuseppe L.
Abstract: This paper studies the interaction between the solid and liquid phase in a brine and ice system which can explain why ice can both be generated and melted in the same brine environment. Ice can be generated if the sweet water introduced to a bath of cold brine is carefully controlled but the generated ice will melt if the solid phase is not separated from the liquid phase, which is warmer than the freezing point of the brine environment. Experiments are conducted and the correlation between heat and mass transfer coefficient and brine temperature at various concentrations are found. At lower temperatures, the primary mode of heat and mass transfer is diffusion and convection starts to dominate the processes as temperature increases. In addition, higher brine concentration discourages heat and mass transfer. The temperature range studied in this paper is from the eutectic point of brine (–21.2 °C) to –4 °C and the brine concentrations are 18, 20 and 22 wt%.